Penerapan Budaya Inovasi Dengan Mengadopsi Konsep Kaizen (Continuous Improvement) di PT. Petrosida Gresik - Oldive Meigres Zenit; Sukaris Sukaris (Jurnal Mahasiswa Manajemen, 2020)
Background - Innovation culture is a very important thing to be applied to a company with the purpose of maintaining the existence and survival of the company. The level of success in doing this innovation significantly depends on the ability, skills and interpreting the rapidly changing environment. In addition, employee involvement also influences the success of innovation. Innovation itself is often associated with KAIZEN or in Japanese terms it means "continuous improvement" which emphasizes human effort, morals, communication, training, cooperation, empowerment and self-discipline. Objective - The purpose of this study was to determine the strategy carried out by PT. Petrosida Gresik in motivating its employees to implement an innovation culture and to identify inhibiting factors in its application and what efforts must be made to minimize these obstacles. Design : This study uses qualitative research methods and the informants in this study are employees who are the originators of the application of an innovation culture in the company, and innovators who always innovate in their work. Validity test of the data by using source triangulation and member checking. Findings - From the results of this study, the researcher can conclude that the application of the innovation culture in this company has a positive impact on the survival of the company. Research implications - This study provides a contribution in human resource management related to corporate culture. Research limitations - Cannot interviews with the Manager of Human Resource Department because timing of the research during the Covid19 pandemic.